Study of The Health Promotion Strategy of Community Led Total Sanitation (CLTS) in Kejawan Putih Tambak Village Surabaya City - Joko Prayitno; Sri Widati (Universitas Airlangga, 2018)
Community-Led Total Sanitation (CTLS) is an approach to transform hygienic and sanitary behaviors. There are five pillar of CLTS is Open Defecation Free (ODF), wash hand wih soap, food and beverage management, waste management and management of household waste. The phenomenon that occurre in the kelurahan Kejawan Putih Tambak is still there are 14 of 1.697 houses which do not have a healthy latrine and drain household wastewater into the river. This study examined the health promotion strategy of the CTLS program in kelurahan Kejawan Putih Tambak. This study is a qualitative research with participatory methode and analyzed descriptively. CTLS has five pillars that need to be achieved by the community. In kelurahan Kejawan Putih Tambak pillar of Open Defecation Free (ODF) and pillar of household liquid waste safe management have not been achieved optimally. It is caused by the lack of a policy and there is no a firm commitment to the perpetrators who dispose feces into the river. Moreover, there is no law enforcement as well and no commitment to collect public dues facilitated by the government or private to create appropriate latrine. Therefore, it is necessary to draft new strategies by giving sanction to open defecation perpetrators. making law enforcement, improving community awareness and making commitment to build communal wastewater installation.